2013
DOI: 10.1177/070674371305800707
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of Posttraumatic Stress Disorder and Depression in Relation to Alcohol-Use and Alcohol-Related Problems among Canadian Forces Veterans

Abstract: Objective: Alcohol misuse is common among military veterans affected by posttraumatic stress disorder (PTSD) and depression; however, research to date has provided mixed evidence concerning differential associations among PTSD and depressive symptoms in relation to alcohol misuse. Further, most available studies have examined primarily male samples or have dichotomously grouped participants as either having or not having an alcohol use disorder. Our study sought to explore relations among 2 aspects of alcohol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
14
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 46 publications
3
14
2
Order By: Relevance
“…That study also revealed that depressive symptoms accounted for unique variance in reported alcohol-related problems and quantity or frequency of alcohol use among male veterans. In contrast, among female veterans, neither PTSD nor depressive symptoms were found to account for significant variance in measures of alcohol-related problems or quantity or frequency of alcohol use (40). In our study, we found that avoidance symptoms of PTSD were associated with alcohol-related problems.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…That study also revealed that depressive symptoms accounted for unique variance in reported alcohol-related problems and quantity or frequency of alcohol use among male veterans. In contrast, among female veterans, neither PTSD nor depressive symptoms were found to account for significant variance in measures of alcohol-related problems or quantity or frequency of alcohol use (40). In our study, we found that avoidance symptoms of PTSD were associated with alcohol-related problems.…”
Section: Discussioncontrasting
confidence: 98%
“…In our study, we found that avoidance symptoms of PTSD were associated with alcohol-related problems. The difference between our study and the previously mentioned study (40) in terms of symptoms of a cluster of PTSD might have resulted from trauma types and severity. As the study mentioned earlier was conducted with veterans exposed to severe trauma from combat compared to other types of trauma, hyperarousal symptoms of PTSD might come into prominence in contrast to avoidance symptoms of PTSD observed here.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Additionally, participants in the gulf war were also overrepresented in the sample; countries not involved in wars do not have such high prevalences of PTSD [32]. However, a recent publication by Fetzner et al [33] showed that, among Canadian armed forces involved in different combat missions, alcohol misuse and depression were more frequent than among Canadian military personnel not involved in combat operations, suggesting that any war-related activity may cause psychological problems and burdens. …”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that posttraumatic stress symptoms and alcohol misuse are significant problems among military personnel (Fetzner et al, 2013; Goodwin et al, 2012; Sundin et al, 2011). This appears to be a notable issue for Veterans exposed to combat, particularly for those deployed to Afghanistan (Operation Enduring Freedom: OEF) and Iraq (Operations Iraqi Freedom: OIF).…”
mentioning
confidence: 99%